2021
DOI: 10.3390/ijms22189731
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Metabolic Effects of Glycomacropeptide

Abstract: For many years, the main nitrogen source for patients with phenylketonuria (PKU) was phenylalanine-free amino acid supplements. Recently, casein glycomacropeptide (GMP) supplements have been prescribed due to its functional and sensorial properties. Nevertheless, many doubts still persist about the metabolic effects of GMP compared to free amino acids (fAA) and intact proteins such as casein (CAS). We endeavour to compare, in rats, the metabolic effects of different nitrogen sources. Twenty-four male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Administering GMP in combination with glucose to prediabetic patients resulted in a notable reduction in postprandial glycemia, suggesting a modulatory effect on glucose metabolism. This finding hints at GMP's potential in managing blood sugar levels, which could have implications for metabolic disorders such as diabetes (Pena et al, 2021;Sauvé et al, 2021). Furthermore, investigations using animal models have unveiled GMP's possible role in combating obesity.…”
Section: Other Effectsmentioning
confidence: 89%
“…Administering GMP in combination with glucose to prediabetic patients resulted in a notable reduction in postprandial glycemia, suggesting a modulatory effect on glucose metabolism. This finding hints at GMP's potential in managing blood sugar levels, which could have implications for metabolic disorders such as diabetes (Pena et al, 2021;Sauvé et al, 2021). Furthermore, investigations using animal models have unveiled GMP's possible role in combating obesity.…”
Section: Other Effectsmentioning
confidence: 89%
“…A putative explanation is that amino acids, especially leucine, which is contained in large amounts in Phe-free amino acid supplements, act as important triggers of insulin secretion [21]. In a study on a murine model, Pena et al [22] analysed the chronic effects of casein (CAS), free amino acids (L-AAs), and GMP on glycaemic metabolism by assessing its biochemical markers in blood. No significant differences in glycaemia were observed among the three treatments, while insulin levels were significantly higher in rats fed with GMP than those fed with L-AAs, in contrast to what was expected.…”
Section: Impact On Carbohydrate Metabolism and Glycaemiamentioning
confidence: 99%
“…A recent meta-analysis showed that growth impairment is still a reality in some patients with PKU under a Phe-restricted diet, while the same was not found in those patients not requiring dietary restriction [8]. The different absorption kinetics of AAs from different sources may impact nitrogen balance and involve several distinct metabolic pathways [10]. Slowly digested proteins provide the efficient postprandial utilization of dietary nitrogen [11], whereas free AAs are absorbed too rapidly to support anabolic requirements [12].…”
Section: Introductionmentioning
confidence: 99%